From Drug Literature Evaluation to Evidence-Based Medicine: Transforming the Focus of a First Year Pharmacy Curriculum - Shannon Reidt; Keri Hager; James Beattie; Amy Pittenger; Maureen Smith; Kristin Janke (University of Minnesota Libraries Publishing, 2016)
This case study describes a longitudinal curricular sequence implemented to teach evidence-based medicine (EBM) skills. The longitudinal sequence is innovative in its approach, design, and assessment of EBM. This approach moves away from the conventional strategy of teaching drug information and drug literature evaluation as stand-alone courses and instead embraces the EBM Framework and its use in the context of authentic problem solving. The EBM Framework-Ask, Acquire, Appraise, and Apply-was used as the basis for defining seven EBM skills. These skills were targeted in the evidence-based, integrated design of 17 learning episodes delivered with eight faculty members through six courses in the first year. Student perceptions of relevance of EBM and performance on assessments and learning activities throughout the sequence suggest that integrating EBM across the first year of the curriculum is an effective strategy for teaching EBM skills. Three themes emerged from analysis of the data and experience, including the need for: a strong teaching team, a whole task approach with a focus on solving authentic problems, and care in interpreting the progression of assessments and patterns of student performance. Through instructor observations and peer review, the longitudinal sequence has been refined and has had an impact on the rest of the curriculum.   Type: Case Study